(untitled) (Research, Society and Development, 2020)
The availability of light is one of the factors that most limits the photosynthesis of juvenile trees in the understory of the forest. The study was carried out in the Mata do Pau-Ferro State Park, located in the city of Areia, PB. The objective of this study was to evaluate how gas exchanges occur in individuals of Psychotria colorata (Willd. Ex Roem & Schult.), Senna georgica Irwin & Barneby, Himatanthus phagedaenicus (Mart.) Woodson, Solanum swartzianum Roem. & Schult, Psychotria carthagenensis Jacq.e Psychotria hoffmannseggiana (Willd. ex Schult.) in the understory of a remnant of Mata Atlântica. The rate of photosynthesis (A), transpiration (E), stomatal conductance (Gs), internal CO2 concentration (Ci) leaf temperature-air temperature (°C), and internal carbon (Ci), instantaneous efficiency of water use (EUA) (A/E), Intrinsic efficiency of water use (EiUC) (A/Gs) and the intrinsic efficiency of carboxylation (ratio A/Ci). The rates of maximum photosynthesis (A), photosynthesis (E) and stomatal conductance (Gs) were shown to be influenced by the time of day, as there was no interference of external factors in the diurnal patterns of gas exchange, variations are due to endogenous factors, probably due to the circadian rhythm. The parameter of the gas exchange of sub-forest species responds differently, in the small variations in the luminosity levels of the forest understory